An in situ study of chemical-mechanical polishing behaviours on sapphire (0001) via simulating the chemical product-removal process by AFM-tapping mode in both liquid and air environments. Issue 42 (19th October 2018) - Shi, Xiaolei; Xu, Li; Zhou, Yan; Zou, Chunli; Wang, Rongrong; Pan, Guoshun
Abstract : We present an in situ study of chemical-mechanical polishing behaviours on sapphire (0001) via simulating the chemical product-removal process by AFM-tapping mode. Abstract : Chemical-mechanical polishing (CMP) has drawn significant attention as one of the most advanced techniques for achieving an atomic-level smooth surface. However, the mechanism of CMP is still unclear, and the in situ characterization of CMP behaviors at the nanoscale has been a challenge for decades. In this study, we, for the first time, report an in situ study of CMP behaviors on sapphire (0001) via simulating the chemical product-removal process by using atomic force microscopy (AFM) in tapping mode. Through a combination of intensive experimental measurements and detailed structural characterizations, it is shown that the AFM probe in tapping mode can act as a polishing abrasive to realize simultaneous imaging and chemical product removal on sapphire (0001), thus achieving successful in situ characterizations in both liquid and air environments. This work fills in gaps relating to fundamental CMP mechanisms, and provides a new perspective for the study of CMP behaviors on different materials.